[18F]Fluorine-Labeled Pharmaceuticals: Direct Aromatic Fluorination Compared to Multi-Step Strategies - Krüll, Jasmin; Heinrich, Markus (Asian Journal of Organic Chemistry, 2019)
Positron emission tomography (PET) presents an important tool for medicinal and pharmaceutical investigations, with applications ranging from fundamental research to the diagnosis of a broad variety of diseases. Crucial for the use of this technique is, however, a robust labeling strategy for the preparation of the required radiolabeled compound. For 18-fluorine-labeling, which represents the most widely applied method in this field, it is interesting to note that a kind of paradigm change occurred over the last years. While multi-step labeling strategies were the preferred approach for many decades, mainly due to the lack of suitable leaving groups for direct [ 18 F]fluorination reactions, the synthetic tools to achieve the highly attractive direct 18-fluorine-labeling rapidly increased recently. This focus review points out a comparison between the multi-step approaches and the newly developed direct fluorination strategies available for nucleophilic 18-fluorination of carbocyclic aromatic systems, including a discussion of advantages and limitations.
CRIS-Team Scopus Importer:2019-05-28
Keywords: 18-fluorine; fluorination; PET; radiolabeling; radiopharmaceuticals

Microwave-assisted rapid one-pot synthesis of fused and non-fused indoles and 5-[18F]fluoroindoles from phenylazocarboxylates - Krüll, Jasmin; Hubert, Anja; Nebel, Natascha; Prante, Olaf; Heinrich, Markus (Chemistry - A European Journal, 2017)
Substituted indoles can be prepared from phenylazo-carboxylates through a rapid one-pot sequence featuring a microwave-assisted Fischer indole synthesis as key step. As the phenylazocarboxylates may beforehand be modified by mild nucleophilic aromatic substitution, including the introduction of [18F]fluoride, the overall strategy offers an attractive new access to 5-[18F]fluoroindoles.
EVALuna2:13873

Selective Functionalization of Graphene at Defect-Activated Sites by Arylazocarboxylic tert-Butyl Esters - Halbig, Christian E.; Lasch, Roman; Krüll, Jasmin; Pirzer, Anna; Wang, Zhenping; Kirchhof, Jan N.; Bolotin, Kirill I.; Heinrich, Markus; Eigler, Siegfried (Angewandte Chemie International Edition, 2019)
The development of versatile functionalization concepts for graphene is currently in the focus of research. Upon oxo-functionalization of graphite, the full surface of graphene becomes accessible for C-C bond formation to introduce out-of-plane functionality. Herein, we present the arylation of graphene with arylazocarboxylic tert-butyl esters, which generates aryl radicals after activation with an acid. Surprisingly, the degree of functionalization is related to the concentration of lattice vacancy defects in the graphene material. Consequently, graphene materials that are free from lattice defects are not reactive. The reaction can be applied to graphene dispersed in solvents and leads to bitopic functionalization as well as monotopic functionalization when the graphene is deposited on surfaces. As the arylazocarboxylic tert-butyl ester moiety can be attached to various molecules, the presented method paves the way to functional graphene derivatives, with the density of defects determining the degree of functionalization.
CRIS-Team WoS Importer:2019-03-20

Synthesis, Radiosynthesis and Biological Evaluation of Buprenorphine-Derived Phenylazocarboxamides as Novel mu-Opioid Receptor Ligands - Krüll, Jasmin; Fehler, Stefanie; Hofmann, Laura; Nebel, Natascha; Maschauer, Simone; Prante, Olaf; Gmeiner, Peter; Lanig, Harald; Hübner, Harald; Heinrich, Markus (ChemMedChem, 2020)
Targeted structural modifications have led to a novel type of buprenorphine-derived opioid receptor ligand displaying an improved selectivity profile for the mu-OR subtype. On this basis, it is shown that phenylazocarboxamides may serve as useful bioisosteric replacements for the widely occurring cinnamide units, without loss of OR binding affinity or subtype selectivity. This study further includes functional experiments pointing to weak partial agonist properties of the novel mu-OR ligands, as well as docking and metabolism experiments. Finally, the unique bifunctional character of phenylazocarboxylates, herein serving as precursors for the azocarboxamide subunit, was exploited to demonstrate the accessibility of an F-18-fluorinated analogue.
Keywords: azo compounds; bioisosters; buprenorphine; opioid receptors; radiosynthesis

Tuning the Polarity of Antibiotic-Cy5 Conjugates Enables Highly Selective Labeling of Binding Sites - Graßl, Fabian; Konrad, Maike; Krüll, Jasmin; Pezerovic, Azra; Zähnle, Leon; Burkovski, Andreas; Heinrich, Markus (Chemistry - A European Journal, 2023)
Multidrug-resistant bacteria pose a major threat to global health, even as newly introduced antibiotics continue to lose their therapeutic value. Against this background, deeper insights into bacterial interaction with antibiotic drugs are urgently required, whereas fluorescently labeled drug conjugates can serve as highly valuable tools. Herein, the preparation and biological evaluation of 13 new fluorescent antibiotic-Cy5 dye conjugates is described, in which the tuning of the polarity of the Cy5 dye proved to be a key element to achieve highly favorable properties for various fields of application.
CRIS-Team Scopus Importer:2023-07-28
Keywords: antibiotics; cyanines; dye conjugates; fluorescence; microscopy